The Impact of Social Media on Academic Performance Among College Students - Paul (Sr.), Stanley A. V.; Paul (Jr.), Stanley A. V. (Integrated Journal for Research in Arts and Humanities, 2024)
This study investigates the relationship between social media usage and academic performance among college students. Through a comprehensive literature review, theoretical framework analysis, and empirical data collection, the research aims to elucidate how social media engagement influences students’ academic outcomes. Using SPSS for statistical analysis, the study also incorporates case studies from diverse college settings to offer a nuanced understanding of the implications for educational policy.